Currency crises and purchasing power parity in the asian countries: Evidence based on second-generaton panel unit-root tests - Soon S.-V.; Baharumshah A.Z.; Md Shariff N.S.; Ibrahim S. (Malaysian Economic Association, 2024)
This study applies a second-generaton panel unit-root tests to determine the stochastc propertes of real exchange rates for 14 Asian countries. Based on three popular alternatve definitons of a currency crisis, we identfy the several important currency crisis episodes in the region. The purchasing power parity (PPP) hypothesis was overwhelmingly supported after accommodatng these heterogeneous noisy and unstable observatons. Our panel unit-root test that controls for cross-sectonal dependence and is robust to structural breaks confirms that the crisis in all the countries fits well with the second-generaton models of currency crisis, that is, the root cause of the currency crises may not lie in economic fundamentals. PPP relaton emerges when breaks and cross country dependency has been taken into account for these 14 countries.